Agronomic performance of sweet potato cultivars (Ipomoea batatas) in Iporá -Goiás (Research, Society and Development, 2021)
The performance of different genotypes is different according to the environment and production process employed, knowing this behavior is fundamental to obtain good productivity. In this sense, the objective was to evaluate the agronomic and productive performance of different types of sweet potato cultivars, aiming at the selection of more productive cultivars focused on human food. An experiment was carried out in 2014, composed of nine cultivars in a randomized block design (DBC), with three replications. The characteristics of productivity, root shape, mass, length, diameter and residues were evaluated, thus quantifying the non-commercial roots.  The cultivars Brazlandia Roxa, Rubssol, Brazlandia Branca, Beauregard and Princess obtained higher agronomic performance. Thus, these varieties did not differ and presented interesting characteristics to be explored for production destined to human food for their agronomic and production performance, but the choice should be taken into account the ease of implantation and the consumer market that it wishes to achieve.